NUTRITIONAL FACTORS STIMULATING THE FORMATION OF LYSINE DECARBOXYLASE IN ESCHERICHIA COLI - Maretzki, Andrew (J Bacteriol, 1962)
Maretzki, Andrew (Pennsylvania State University, University Park) and M. F. Mallette. Nutritional factors stimulating the formation of lysine decarboxylase in Escherichia coli. J. Bacteriol. 83:720–726. 1962 — Inclusion of complex nitrogen sources in the induction medium was shown to be necessary for the synthesis of appreciable amounts of l-lysine decarboxylase by Escherichia coli B. Hy-case, a commercial acid hydrolyzate of casein, was especially effective in enzyme production, which was assayed manometrically after lysis of the bacteria from without by bacteriophage. Partial fractionation of the Hy-case, identification of the free amino acids, and addition of these amino acids to test media revealed stimulatory effects by methionine, threonine, proline, leucine, and tyrosine. A full complement of amino acids did not match the enzyme levels reached in the presence of Hy-case. Certain peptide fractions obtained from this mixture supplemented the effects of the amino acids in such a way as to suggest direct incorporation of peptide rather than transport or protective roles. Added purines, pyrimidines, iron, and water-soluble vitamins were without effect. Neither carbohydrates nor phosphorylated materials could be detected in the stimulatory fractions.